Autoantibodies in a Three-Year-Old Girl with Visceral Leishmaniasis: A Potential Diagnostic Pitfall - Gholamreza Pouladfar; Zahra Jafarpour; Amir Hossein Babaei; Bahman Pourabbas; Bita Geramizadeh; Anahita Sanaei Dashti (Case Reports in Infectious Diseases)
Visceral leishmaniasis (VL), a life-threatening parasitic infection, is endemic in the Mediterranean region. Diagnosis of VL is based on epidemiologic, clinical, and laboratory findings. However, sometimes, clinical features and laboratory findings overlap with those of autoimmune diseases. In some cases, autoantibodies are detected in patients with VL and this could be a potential diagnostic pitfall. In this study, we have reported on a three-year-old girl from a VL-endemic area in Iran, who presented with prolonged fever and splenomegaly. Bone marrow examination, serologic tests, and the molecular PCR assay were performed; however, results were inconclusive. The levels of anti-double stranded DNA, cytoplasmic antineutrophil cytoplasmic autoantibody, and perinuclear antineutrophil cytoplasmic autoantibody were elevated and, at the end, splenic biopsy was performed. The splenic tissue PCR test detected the DNA of Leishmania infantum. The patient’s condition improved with anti-Leishmania therapy, and the autoantibodies disappeared within the following four months. Clinical presentations and laboratory findings of VL and autoimmune diseases may overlap in some patients.